" Self, Identity, and the American Experience: Willa Cather's Literary Perspective " (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This research endeavor undertakes an in-depth examination of the "Emerging Self in the Characters of Willa Cather's Selected Novels" through the lens of her profound "Theories of Self and Identity". The study employs a descriptive survey method, augmented by historical research, to meticulously analyze the character development and self-realization processes in Cather's novels. By integrating these research approaches, this investigation aims to provide a nuanced understanding of Cather's literary exploration of the human self, shedding light on the intricate dynamics of identity formation, autonomy, and the quest for individuality in her works.